The functional impact of LGI1 autoantibodies on human CA3 pyramidal neurons - Laura Monni; Hans-Christian Kornau; Alice Podestà; Rosanna P. Sammons; Andrea Sannio; Alexander Stumpf; Thilo Kalbhenn; Matthias Simon; Thomas Sauvigny; Julia Onken; Harald Prüss; Jörg R. P. Geiger; et al. (Proceedings of the National Academy of Sciences, 2026)
Autoantibodies against leucine-rich glioma inactivated 1 protein (LGI1) lead to limbic encephalitis, a rare neurological autoimmune disorder characterized by faciobrachial dystonic seizures and memory deficits. While animal models provide precious insights into the mechanisms of LGI1 autoantibody action, species-specific confirmation is lacking. In this study, we investigated the effects of patient-derived LGI1 monoclonal antibodies (LGI1 mAb) on CA3 pyramidal neurons using cultured ex vivo human hippocampal slices, providing a unique platform to study disease mechanisms in a homologous, clinically relevant context. Under incubation conditions, human CA3 neurons preserved their morphology, were intrinsically excitable and received spontaneous excitatory currents with large amplitudes and frequencies suggestive of “giant” AMPA receptor-mediated currents. In slices exposed to LGI1 mAb, human CA3 pyramidal neurons displayed increased action potential (AP) firing frequency, mirroring the effects observed with the K v 1.1 channel blocker dendrotoxin-K (DTX-K). This increase likely resulted from a decreased K v 1.1 channel activity at the axonal initial segment, as indicated by alterations in AP properties, including spike latency at rheobase and depolarizing ramp slope. Differences between LGI1 mAb and DTX-K effects on some AP properties suggested distinct mechanisms of action and emphasized the need for further exploration of downstream pathways. Our findings underscore the importance of species-specific confirmatory studies of disease mechanisms and give insight into possibilities and limitations of human hippocampal slice cultures as a translational model for the investigation of disease mechanisms beyond epilepsy, including the effects of pharmacological compounds and autoantibodies.